Ar+ plasma-induced damage to DNA in bacteriophage lambda: implications for the arrangement of DNA in the phage head. - Mendelson, E C (1992)
Bacteriophage lambda was bombarded with low-energy Ar+ ions with the goal of determining whether particular regions of the DNA genome are found preferentially in the outer portion of the packaged DNA mass. The strategy was to fragment the DNA selectively near the surface of the virus by exposing intact phage to Ar+ ions energetic enough to break covalent chemical bonds in DNA but not energetic enough to penetrate deeply beneath the viral capsid shell. Broken DNA was then isolated, and its genomic origin was identified by Southern hybridization to mapped restriction fragments of lambda DNA. Analysis of such Southern blots revealed that all regions of the lambda genome were represented among the small DNA fragments generated during all times of Ar+ bombardment examined. Depending on the duration of exposure, however, particular regions of the genome were found to be enriched in the small-fragment population. After short periods of exposure, sequences from the leftmost 10% and from the right half of the standard genetic map were enriched in the broken-DNA fraction. Among sequences in the right half of the genome, the enrichment was progressively more pronounced beginning in the middle of the genetic map and proceeding toward the right end. In phage bombarded for longer periods of time, rightward sequences were preferentially depleted in the small-fragment population. In contrast, when Ar+ bombardment was carried out with free lambda DNA rather than intact phage, small DNA fragments arose uniformly from all regions of the genome at all times of exposure examined. The results indicate that in the intact phage, DNA sequences from the right half and from the very leftmost regions of the genome have a tendency to lie closer to the capsid than does the remainder of the genome. Since DNA is packaged into the prohead beginning at the left end, our results suggest that packaging occurs in such a way that newly entering DNA tends to be disposed externally to that packaged at earlier times.